FAKTOR YANG MEMPENGARUHI PENYERAPAN TENAGA KERJA DI JAWA TENGAH TAHUN 1997-2021 - Setyo, Septa Tri; Juliprijanto, Whinarko (Jendela Inovasi Daerah, 2023)
This study aims to determine and analyze the factors that affect the absorption of labor in Central Java. The type of data in this study uses time series and secondary data with the study period from 1997 to 2021. The estimation method used is the Error Correction Model (ECM) which is able to show long-term and short-term effects. The results show that in the long term the variables of the provincial minimum wage, domestic investment, and foreign investment together have a significant and significant effect on employment. Meanwhile, in the short term, only domestic investment variables are influential and significant with a probability value of 0.0418 with a confidence level of 0.05. This situation indicates that in the short term changes in the value of domestic investment will have a positive effect on employment.